Scholarly Communication: Science Librarians as Advocates for Change. - Elizabeth C. Turtle; Martin P. Courtois (Issues in Science and Technology Librarianship, 2007)
Science librarians are in a unique position to take a leadership role promoting scholarly communication initiatives and to aid in making scientific information more accessible. This article outlines steps and identifies resources that science librarians can employ to become scholarly communication advocates on their campuses.